(untitled) (Journal of the College of Basic Education, 2023)
The issue of preserving the environment is a vital issue that is included in the legislative and scientific aspects. technology, and most importantly of all, it is no longer an educational issue in the first place, depending on the quality Educational for people at various levels to create environmental awareness, environmental values ​​and trends, and good behavior. with her. Because man possesses capabilities that enable him to exploit the environment and destroy it at the same time, which requires Protecting it from a possible catastrophe, and this protection requires, first, the development of specific legislation and firmness in